Environmental change and human security : (Springer, 2008)
This book focuses on the linkage between human and environmental security and takes both a conceptual and a pragmatic approach to complex environmental issues (such as soil erosion, desertification, water degradation, demographic shifts, food security and agricultural prospects, urbanization trends, hazard-induced migrations) that affect human security. The book summarizes the collective work of both natural and social science disciplines in regard to how best address, mitigate, adapt, or achieve resilience in the face of changing environmental conditions.The book is written in an accessible style to discuss the concept of security from both subjective and objective perspectives.